Assessment of Connections Between Knowledge- Based Economy Characteristics and Selected Macroeconomic Categories in the European Union's Countries by Means of Panel Models; Ocena zalezṅosći miedzy charakterystykami gospodarki opartej na wiedzy a wybranymi kategoriami makroekonomicznymi w krajach Unii Europejskiej - Edyta Dworak (Comparative Economic Research. Central and Eastern Europe, 2011)
The aim of the article is to analyze the impact of knowledge-based economy variables on the selected macroeconomic categories - the share of total investments in GDP and the employment rate- in European Union's countries in the years 2000-2007, conducted with application of panel models. Directions of changes occurring in the world economy in recent years show the transformation of the industrial economy into a knowledge-based economy, using the technological and innovative potential. The most vital determinants of economic development are research and development expenditures, effects of this activity revealed in the form of innovations and human capital. Consequently the main subject of research conducted in high developed countries is seeking new sources of innovativeness and methods of creating innovative potential. An essential impact of knowledge and innovations on economic development is also confirmed by the contemporary economics. The aim of the article is to analyze the impact of knowledge-based economy variables on the selected macroeconomic categories - the share of total investments in GDP and the employment rate- in European Union's countries in the years 2000-2007, conducted with application of panel models. – – Kierunki przemian w gospodarce sẃiatowej, zachodzacych w ostatnich latach, wskazuja na przechodzenie od gospodarki ery przemysłowej do gospodarki wiedzochłonnej, opartej na potencjale technologicznym i innowacyjnym. Czynnikami decydujacymi o rozwoju gospodarczym staja sie działalnosćb́adawczo - rozwojowa (B+R), działalnosćínnowacyjna i tzw. kapitał ludzki. W konsekwencji głoẃnym przedmiotem badanṕrowadzonych w krajach wysoko rozwinietych jest poszukiwanie zŕod́eł innowacyjnosći i metod budowania potencjału innowacyjnego, ktoŕe staja sie podstawa kreowania gospodarki opartej na wiedzy. Istotny wpływ wiedzy i innowacji na rozwoj́ gospodarczy potwierdza roẃniezẇspoĺczesna ekonomia, ktoŕa dowodzi, zė postep techniczny oraz akumulacja wiedzy naukowo-technicznej i kapitału ludzkiego oddziałuja na rozwoj́ wspoĺczesnych gospodarek w wiekszym stopniu nizṫradycyjne czynniki produkcji. Celem artykułu jest analiza wpływu zmiennych opisujacych gospodarke oparta na wiedzy na podstawowe kategorie makroekonomiczne - udział całkowitych inwestycji w PKB i stope zatrudnienia - w krajach Unii Europejskiej (z podziałem na kraje UE-15 i nowe kraje członkowskie UE) w latach 2000-2007, przeprowadzona w oparciu o modele panelowe.
Keywords: 330